Multiple Sclerosis Treatments Affect Monocyte-Derived Microvesicle Production - Blonda, Maria; Amoruso, Antonella; Grasso, Roberta; Di Francescantonio, Valeria; Avolio, Carlo (Frontiers in Neurology, 2017)
ABSTRACT Microvesicles (MVs) are released by immune cells especially of the myeloid lineage upon stimulation with ATP on its cognate receptor P2X7, both in physiological and pathological conditions. In Multiple Sclerosis (MS) the role of MVs remains little investigated. We aimed to compare the release of MVs in peripheral blood monocytes from MS patients with healthy donors (HDs) and to see how current MS treatment may affect such a production. We also assessed the treatment effect on M1 and M2 monocyte polarization and on the inflammasome components. Spectrophotometric quantification was performed to compare monocyte-derived microvesicles from 20 untreated relapsing-remitting MS patients and 20 healthy donors (HDs) and to evaluate the effect of different treatments. Subgroups of 9 IFNb and of 5 Teriflunomide treated MS patients were evaluated at baseline and after 2, 6 and 12 months of treatment. Six MS patients assuming Fingolimod, after switching from a first line therapy, were included in the study and analyzed only at 12 months of treatment. MVs analysis revealed that monocytes from MS patients produced vesicles in higher amounts than controls. All treatments reduced vesicle production but only Teriflunomide was associated with a down-regulation of P2X7R and inflammasome components expression. The therapies modulated mRNA expression of both M1 and M2 monocyte markers. Our results, suggesting new molecular targets for drugs currently used in MS, may potentially provide useful novel evidence to approach the disease.